Irish writers in the Irish American press, 1882-1964 - Butler, Stephen G. (University of Massachusetts Press, 2018)
"Literary anthologies feature many of Ireland's most well-known authors, Oscar Wilde, W.B. Yeats, J.M. Synge, George Bernard Shaw, Seán O'Casey, James Joyce, and Brendan Behan among them. While a number of notable scholars have contended that middle-class Irish Americans rejected or ignored this rebellious group of poets, playwrights, and novelists in favor of a conservative Catholic subculture brought over with the mass migration of the mid-nineteenth century, Stephen G. Butler demonstrates that the transatlantic relationship between these figures and a segment of Irish American journalists and citizens is more complicated--and sometimes more collaborative--than previously acknowledged. Irish Writers in the Irish American Press spans the period from Oscar Wilde's 1882 American lecture tour to the months following JFK's assassination and covers the century in which Irish American identity was shaped by immigration, religion, politics, and economic advancement. Through a close engagement with Irish American periodicals, Butler offers a more nuanced understanding of the connections between Irish literary studies and Irish American culture during this period"--